Interplay between the metal- support interaction and stability in Pt/ Co3O4(111) model catalysts - Lykhach, Yaroslava; Faisal, Firas; Skala, Tomas; Neitzel, Armin; Tsud, Nataliya; Vorokhta, Mykhailo; Dvorak, Filip; Beranova, Klara; Kosto, Yuliia; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Materials Chemistry A, 2018)
The interplay between the metal-support interaction and stability with respect to sintering has been investigated for Pt nanoparticles supported on well-ordered Co3O4(111)/Ir(100) films in UHV and under oxidizing conditions by means of synchrotron radiation photoelectron spectroscopy (SRPES) and near ambient pressure X-ray photoelectron spectroscopy (NAP XPS). The electronic metal-support interaction between Pt and Co3O4(111) associated with charge transfer results in partial reduction of Co3O4(111) yielding partially oxidized Pt+ species at the interface. The stability of the supported Pt particles is coupled with the oxidation state of Pt+ species, which can be reduced or oxidized depending on the Pt coverage and reactive environment. Annealing of Pt/Co3O4(111)/Ir(100) in UHV triggers the reduction of Pt+ species. At higher temperature, reverse spillover of oxygen to the Pt nanoparticles is accompanied by reduction of Co3O4(111). Under these conditions, the oxidation state of Pt+ species depends strongly on Pt coverage. Thus, at low Pt coverage (0.3 ML Pt), Pt+ is converted to Pt4+, at intermediate coverage (1.3 ML Pt), Pt+ remains stable, and at high Pt coverage (1.93 ML), Pt+ is reduced to Pt-0. Sintering of Pt particles is associated with the reduction of the Pt+ species. This process is prevented under oxidizing conditions due to the formation of an interfacial oxide PtOx. The formation of an interfacial PtOx is observed at 300 K under exposure to 1 x 10(-6) mbar O-2 at Pt coverages below 1.3 ML. Using NAP XPS, we observe the formation of an interfacial PtOx at high Pt coverage (2.0 ML) in an oxygen atmosphere (1 mbar) at 300 K while the formation of surface PtOx is kinetically hindered and occurs above 550 K only.